Bilingualism : a study of the dominant language of Chinese undergraduates through their internal uses - Low, Chew Yun (Universiti sains malaysia, 1984)
Since the end of the eighteenth century, language has come to be copiously and comprehensively studied by philosophers, linguists, semanticists and literary critics. Psychologists have been concerned with how a child acquires his first language and with the stages of speech development in human beings. Some political scientists and historians have been interested in language as related to national origins and ethnic boundaries, the relationship between language and nationalism, and other aspects of political manipulation and control. While these linguistic studies made reference to language in its different context respectively, other social scientists have sought explanation of language in its social context especially in terms of its social and societal relationships, implications, functions and effects. Social interaction and communication through the use of language can be analysed in different approach, context and purpose